2017
DOI: 10.1111/eci.12839
|View full text |Cite
|
Sign up to set email alerts
|

The association of profilin‐1 levels with survival in chronic kidney disease

Abstract: This is the first study that demonstrates the serum profilin-1 is independently associated with endothelial dysfunction, cardiovascular events and survival in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…Therefore, myosin is diffusely activated in stress fibers, extending to focal adhesions, immobilizing the fibroblast, and promoting myofibroblast differentiation in fibrotic lung progression [23][24][25]. A clinical research reported that Pfn1 is highly expressed in endothelial cells and in the serum of patients with decreased eGFR [11]. Our study also observed increased Pfn1 expression in TH1 cells treated with P-cresol.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Therefore, myosin is diffusely activated in stress fibers, extending to focal adhesions, immobilizing the fibroblast, and promoting myofibroblast differentiation in fibrotic lung progression [23][24][25]. A clinical research reported that Pfn1 is highly expressed in endothelial cells and in the serum of patients with decreased eGFR [11]. Our study also observed increased Pfn1 expression in TH1 cells treated with P-cresol.…”
Section: Discussionsupporting
confidence: 71%
“…Pfn1 regulates cellular homeostasis and maintains cytoskeletal structure. However, previous clinical studies verified that Pfn1 is highly expressed in endothelial cells and in the serum of CKD patients with decreased eGFR [11]. These results indicate that, in CKD patients, the overexpression of Pfn1 disrupts the homeostasis of actin dynamics and increase F-actin in renal proximal tubule epithelial cells.…”
Section: Ivyspringmentioning
confidence: 83%
See 1 more Smart Citation
“…Profilin 1 played an important role in regulation of actin polymerization and cytoskeleton remodeling ( Stritt et al, 2018 ). Serum profilin 1 was independently associated with endothelial dysfunction, cardiovascular events and survival in patients with chronic kidney disease ( Eroglu et al, 2017 ; Li X. et al, 2018 ). Mutations in profilin 1 led to familiar amyotrophic lateral sclerosis ( Daigle et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A PNF1 atua como um regulador complexo de montagem de actina monomérica (G-actina) em filamentos (F-actina) (Bubb et al 2003;Pollard and Borisy 2003). Esta proteína foi encontrada aumentada na urina de pacientes com doença renal policística e a PNF1 sérica foi independentemente associada com disfunção endotelial, eventos cardiovasculares e sobrevida de pacientes com DRC (Bakun et al 2012;Eroglu et al 2017). A PNF1 já foi nitrada in vitro e verificado que a nitração inibe a sua propriedade sequestradora de actina, reduzindo a concentração de monômero de actina ligada a ela (Kasina et al 2005).…”
Section: )unclassified